Mass growth of massive quiescent galaxies in the Illustris TNG simulation - Bendegúz Koncz; András Péter Joó (Acta Polytechnica)
Interactions between galaxies could potentially lead to increased rates of star formation within these galaxies, potentially leading to the occurrence of multiple core-collapse supernovae and the ejection of hot gas. Numerical simulations are crucial for understanding the formation and evolution of galaxies. Using the IllustrisTNG cosmological simulation, we show how the massive quiescent galaxies evolve in cosmic times. We use the merger tree from the TNG300-1 simulation to demonstrate the impact of dwarf galaxies on the mass augmentation of these galaxies during the early Universe. We made a galaxy sample with restrictions on the specific star formation rate log(sSFR) and mass (M). Most of the mergers have a <1:1 000 ratio to the host galaxy and 5–25% of the falling material is connected to the merger events. These results show that dwarf galaxies could play a significant role in the growth of these massive galaxies.